The Role of Servant Leadership in Creating a Positive School Climate - Osias Kit T. Kilag; Felix M. Diano; Marsha H. Malbas; Debra P. Mansueto; Se P. Villar; John Michael Sasan (International Journal of Integrative Sciences, 2023)
This study investigates the role of servant leadership in creating a positive school climate. A quantitative research design was used to examine the relationship between servant leadership and school climate, including the effects of servant leadership on student academic achievement, teacher job satisfaction, and school culture. The study was conducted in several schools in a particular district, and data were collected using a survey questionnaire from 40 teachers and 1000 students. Data were analyzed using descriptive and inferential statistics. The findings suggest that there is a significant positive correlation between servant leadership and teacher job satisfaction (r = 0.55, p < 0.01), school culture (r = 0.62, p < 0.01), and academic achievement (r = 0.45, p < 0.01). The results indicate that servant leadership practices contribute to the development of a positive school climate. The study provides support for the notion that servant leadership is a viable leadership approach in schools that can contribute to the development of a positive school climate